Handbook of Diversity Competence (Springer Nature, 2025)
This open access handbook provides the most current overview of the discussion on diversity competence, with a focus on Europe. Diversity competence has become a key area of interdisciplinary study because of the increasingly intercultural nature of institutions and organisations across the world. This important handbook reviews the conceptual and theoretical foundations of this concept and reflects on the scope of its application. It provides directions for further research in the theory, research and practice of diversity competence and includes country-wise perspectives as well. An international team of researchers brings together insights from research and best practice in psychology, cultural sciences, economics, pedagogical sciences, sociology, social work, medicine, theology, politics and law. This is an important resource for a wide readership of students, researchers and practitioners who research on or work with people from diverse cultures.